2017
DOI: 10.1155/2017/4037086
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Ameliorates Airway Inflammation in an Established Murine Model of Asthma by Inhibiting the mTORC1 Signaling Pathway

Abstract: Astragaloside IV (AS-IV), a main active constituent of Astragalus membranaceus, has been confirmed to have antiasthmatic effects. However, it remained unclear whether the beneficial effects of AS-IV on asthma were attributed to the mTOR inhibition; this issue was the focus of the present work. BALB/c mice were sensitized and challenged with ovalbumin followed with 3 weeks of rest/recovery and then reexposure to ovalbumin. AS-IV was administrated during the time of rest and reexposure. The characteristic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Besides, infiltration and levels of inflammatory cells and AHR were also significantly upregulated in OVA‐induced mice (Figure ). These phenomena are corresponding to mouse model of asthma in previous studies (Jin et al, ; Qiu et al, ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Besides, infiltration and levels of inflammatory cells and AHR were also significantly upregulated in OVA‐induced mice (Figure ). These phenomena are corresponding to mouse model of asthma in previous studies (Jin et al, ; Qiu et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…Besides, some studies showed AS‐IV attenuates the eosinophilic infiltration in ovalbumin‐induced asthma (Du et al, ; Gu, Jiang, Wang, Du, & Cai, ; Huang, Tang, Wang, & Song, ). Previous study used 20–40 mg/kg doses of astragaloside IV (AS‐IV) daily to treat OVA‐induced mouse model of asthma and had different degree levels to inhibit asthma syndrome (Jin et al, ). Cytokine levels, IL‐4 and ‐5, in BALF of mouse model and airway inflammation in the lung tissue were more dominantly affected by 40 mg/kg dose daily of AS‐IV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations